Psychological Effects of Subfertility on Women - Sohaib Arif, Nida Khurshid, Maryam Manzoor, Laraib Sajjad, Ammarah Mehmood, Muhammad Awais Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Out of all the human beings present the 20% are infertile. The 10-15 couple experience difficulties in conceiving. Study design: It is a cross-sectional study with statistical approach, conducted at Department of Obstetrics and Gynaecology, Indus Hospital Jubliee Town, Lahore. Objective: The study aimed to study the psychological effects of subfertility on women. Material and Methods: The study was conducted on the 80 female patients under treatment as they are not conceiving after repeated unsuccessful attempts. The female attended the gynecology department of our institute teaching hospital. The review board of the hospital approved the study. The average duration of not getting pregnant was 2 years in these participants. The study was conducted for 6 month from January 2022 to June 2022. Results: The average duration of not getting pregnant was 2 years in these participants. Most of the women reported that they previously had no child. However, there were 14% of them that had one child already. The mean of the state anxiety in these female participants came out to be 44 with a SD of 9.5. And the trait anxiety was reported to be 41 with SD of 7.1. Both of these features were found to be higher in case of sub fertile female patients undergoing fertility treatment. The level of stress was shown to be high in case of marital issues as compare to the social stress and personal stress. The educational level was found to be statistically linked to the participant’s stress level. However, the financial condition and age was not found to be linked to stress in sub fertile female. Conclusion: The women undergoing fertility treatments as they are not being successful to conceive suffers from stress, anxiety and depression like psychological issues. The societal pressure and low educational level are some of the factors that elevates the psychological issues in sub fertile female. If proper professional guidance is given to the patients it can help them cope with the fertility issue stress free. Therefore, counseling is a much helpful thing to accept and face the challenges of sub fertility. Keywords: Subfertility, psychological status, stress, anxiety and education level.